L’Impersonale tra persone e cose - Esposito, Roberto (Philosophy Kitchen - Rivista di filosofia contemporanea, 2016)
Ever since its beginning, our civilization has been based on a strict, unequivocal distinction between persons and things, founded on the instrumental domination of persons over things. But what we are witnessing in legal, economic, and technological practice is a reversal of perspective: some categories of persons are assimilated into things, while some typologies of things are taking on a personal profile. There is an escape route out of this paradox, constituted by a new point of view founded on the body. Being neither a person nor a thing, the human body becomes the decisive element in rethinking the concepts and values that govern our philosophical, legal, and political lexicons.